A CALL FOR MENTORING OF MEDICAL STUDENTS IN THE BACKDROP OF INTEGRATED CURRICULUM - Sadiq, Naushaba; Aurangzeb, Wajeeha; Farooq, Ayesha; Rauf, Shahid; Salman, Syyeda (Journal of Ayub Medical College Abbottabad, 2013)
Background: Integrated Modular Teaching program was introduced at Foundation University Medical College in 2009. The concept of integrated modular teaching was new to the faculty and students. A need was felt by Department of Medical Education for establishing a mentoring system in order to have a better understanding of students’ problem, to provide them continuous support and to make them sail smoothly through this new system. This study was conducted for need assessment and to gain students’ perspectives regarding establishing a mentoring system. Methods: It was a descriptive cross-sectional study. A 5-point Likert scale questionnaire was administered to third year medical students of academic year 2010-14, who underwent the new integrated curriculum. The questionnaire explored the students’ view regarding the need of mentoring platform in the institution as part of formal education. The questionnaire focused on the students’ knowledge of mentoring, their experience with informal mentoring, desire for mentoring and environment for mentoring. Data were analysed using SPSS-10. Results: Eighty-six percent of the participants agreed to the statement that there is a need for a personal, confidential support system. Conclusion: Students are aware of benefits of mentoring and seek informal mentoring from faculty and senior colleagues. There is need of formal mentoring program at institutional level. Keywords: Mentoring, Need assessment, Likert scale, Integrated curriculum, Medical Education